2017
DOI: 10.1038/s41598-017-16328-y
|View full text |Cite
|
Sign up to set email alerts
|

Generation of gene-edited rats by delivery of CRISPR/Cas9 protein and donor DNA into intact zygotes using electroporation

Abstract: The generation of gene-edited animals using the CRISPRs/Cas9 system is based on microinjection into zygotes which is inefficient, time consuming and demands high technical skills. We report the optimization of an electroporation method for intact rat zygotes using sgRNAs and Cas9 protein in combination or not with ssODNs (~100 nt). This resulted in high frequency of knockouts, between 15 and 50% of analyzed animals. Importantly, using ssODNs as donor template resulted in precise knock-in mutations in 25–100% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(71 citation statements)
references
References 37 publications
0
67
0
1
Order By: Relevance
“…Up to 500 presumptive zygotes can be microinjected one by one into the cytoplasm (2e5 pl of injection mix) in each session. On the other hand, electroporation has recently been described as an alternative approach to deliver small CRISPR reagents into mouse and rat zygotes [30,31] and it is currently used in our laboratory [28,32]. This procedure avoids the technically demanding microinjection technique allowing a high throughput scheme in the laboratory.…”
Section: Embryo Manipulationmentioning
confidence: 99%
“…Up to 500 presumptive zygotes can be microinjected one by one into the cytoplasm (2e5 pl of injection mix) in each session. On the other hand, electroporation has recently been described as an alternative approach to deliver small CRISPR reagents into mouse and rat zygotes [30,31] and it is currently used in our laboratory [28,32]. This procedure avoids the technically demanding microinjection technique allowing a high throughput scheme in the laboratory.…”
Section: Embryo Manipulationmentioning
confidence: 99%
“…The high fidelity of the homologous recombination pathway can be used to create controlled insertions, deletions and substitution of a single nucleotide or large tracks of genomic DNA by HDR. Although reported in other species [17][18][19] , current literature is scarce for CRISPR assisted ssODN-mediated homologous recombination in ruminant species (i.e., sheep, goats and cattle). Recently, Williams et al 5 reported for the first time the effectiveness of this tool to induce a point mutation in sheep, and Eaton et al 20 described the generation of homozygotes lambs by the insertion of a human mutation into the orthologous sheep locus.…”
Section: Discussionmentioning
confidence: 99%
“…Germline editing with CRISPR-Cas9 has proven remarkably useful for genetically modifying animals (Li et al, 2013;Chapman et al, 2015;Remy et al, 2017). However, germline modifications can produce undesirable developmental phenotypes providing little benefit for studies interrogating gene function in adult animals.…”
Section: Regulable Gene Editing With Inducible Crispr-cas Systemsmentioning
confidence: 99%